Physiological Response of Bali Cattle to Feeding Substitution of Balinese Fermentation Straw - N. Nurdiana; Bahri Syamsuryadi; Abdul Hakim Fattah (Chalaza Journal of Animal Husbandry, 2018)
This study aims to see the physiological response of Bali cattle to the feeding of fermented straw substitution. A total of 12 head of Bali cattle average age five years. This research was conducted from August to September 2017 in Cenrana Village, Kahu Sub-district, Bone District, which is a location in the business of Berdikari Berdikari Mallomo Utama. This study used a randomized block design (RBD) with 4 treatments and 3 replications so that there were 12 experimental units, the procedure was P0: 100% elephant grass + 100% fermentation control, P1: elephant grass 75% + generation fermentation 25%, P2: 50%, elephant grass + 50% fermenting straw, and P3: Elephant grass 25% + 75% fermentation straw. The parameters observed were body temperature, respiration rate, and liver rate. The data obtained were analyzed variance and continued with LRD test. The results showed that the substitution of hay fermentation had a significant effect (P .01) on the physiological response of Balinese cow heart, but no significant effect (P .05) to the body temperature and the rate of respiration of Bali cattle. The conclusion that by giving fermented straw substitution feed provide an effect on heart rate (58.33 / min) with treatment 25% elephant grass + 75% fermented straw in the normal range for Bali cattle.